2022
DOI: 10.3390/foods11131883
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits, Food Applications, and Sustainability of Microalgae-Derived N-3 PUFA

Abstract: Today’s consumers are increasingly aware of the beneficial effects of n-3 PUFA in preventing, delaying, and intervening various diseases, such as coronary artery disease, hypertension, diabetes, inflammatory and autoimmune disorders, neurodegenerative diseases, depression, and many other ailments. The role of n-3 PUFA on aging and cognitive function is also one of the hot topics in basic research, product development, and clinical applications. For decades, n-3 PUFA, especially EPA and DHA, have been supplied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 281 publications
0
19
0
Order By: Relevance
“…reuteri mitigated the HFHS-reduced PUFAs, including C18:2N6, C18:3N6, C20:4N6 (ARA), C22:5N3 (DPA), and C22:6N3 (DHA). PUDF (such as DHA, DPA, and ARA) has shown to prevent and alleviate various diseases, such as hypertension, diabetes, inflammatory, and many other ailments. , Consistent effects were observed for PKP+L. reuteri, but the effect size was weaker than pasteurized PKP–L.…”
Section: Resultsmentioning
confidence: 98%
“…reuteri mitigated the HFHS-reduced PUFAs, including C18:2N6, C18:3N6, C20:4N6 (ARA), C22:5N3 (DPA), and C22:6N3 (DHA). PUDF (such as DHA, DPA, and ARA) has shown to prevent and alleviate various diseases, such as hypertension, diabetes, inflammatory, and many other ailments. , Consistent effects were observed for PKP+L. reuteri, but the effect size was weaker than pasteurized PKP–L.…”
Section: Resultsmentioning
confidence: 98%
“…Wang et al [19] also showed that the PT extract significantly decreases brain and blood inflammation (IL-6) and oxidative stress (lipid peroxidation), which are mechanisms largely involved in cognitive performance. Moreover, microalgae varieties such as PT also contain LC-PUFAs and EPA that have been reported to reduce neuroinflammation and oxidative stress, thereby providing neuroprotection [15][16][17]21,22]. Finally, since guarana contains caffeine, it may improve cognitive performance [11][12][13]73] and help maintain focus and mental energy by stimulating the central nervous system (e.g., blocking adenosine activity) [60].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, unsaturated fatty acids, including monounsaturated fatty acids (MFUA) and polyunsaturated fatty acids (PUFA), are considered essential nutrients for the human body. PUFA exhibit anti-in ammatory properties, promote brain development, and help prevent cardiovascular disease [22], MUFA also offer bene cial effects such as blood sugar regulation, blood lipid control, heart protection, and cholesterol reduction [23]. In this experiment, drinking hydrogen-rich water signi cantly reduced the proportion of C11:0 (SFA) in chicken breast meat and decreased the proportion of C22:1n9 (MUFA), while highly increasing the proportion of C16:1 (MUFA), C18:1n9c (MUFA), and total MUFA.…”
Section: Discussionmentioning
confidence: 99%